37 Postural Instability in Parkinson's Disease: The Association of Cognitive Impairment and Non-Motor Symptoms. (20th December 2019) - Khoo, Tien K; Cusso, Melanie; Sewram, Allka; Pountney, Dean; Donald, Kenneth
Abstract: Introduction: Parkinson's disease (PD) is the second most common neurodegenerative condition after Alzheimer's. Historically considered as a movement disorder, the multitude of non-motor symptoms (NMS) are now a recognised cause of significant disease burden. This study aimed to explore the relationship between postural instability and NMS in PD. Methodology: We recruited individuals (n=100) in South East Queensland with a pre-existing diagnosis of idiopathic PD into this prospective observational study. Motor assessment was performed via the Movement Disorders Society-revised Unified Parkinson's Disease Rating Scale (MDS-UPDRS). Assessment of postural instability was based on the Hoehn & Yahr Scale (H&Y) with a score of ≥3 considered indicative of postural instability. NMS were assessed via the Non-Motor Symptoms Scale (NMSS). Further neuropsychiatric and affective assessment was evaluated with the Geriatric Depression Scale (GDS-15), Geriatric Anxiety Inventory (GAI), Epworth Sleepiness Scale, Pittsburgh Sleep Quality Index (PSQI) and Montreal Cognitive Assessment (MoCA). Results: Cohort demographics comprised of 62% male and 38% female with a mean age of 69.1 years (SD 7.35) and mean H&Y 2.34 (SD 0.59). Sixty four participants were H&Y 1 & 2 whilst 36 participants were H&Y ≥3. Participants with postural instability were significantly older (p = 0.033) and had lower MoCA scores (p=0.039). Among the MoCA domains, only the Visuospatial / Executive domain was associated with postural instability (p= 0.005). Among the NMSS domains, only the sexual function domain was significantly associated with the latter group (p=0.029). GDS scores tended to be higher in the postural instability group (p=0.054) but there was no significance in major depressive disorder (p=0.436). Conclusion: Postural instability in PD is significantly associated with age and cognitive impairment, in-particular frontal lobe function. The association of sexual dysfunction is supportive of the notion that disorders in dopaminergic and non-dopaminergic systems underpin the pathophysiology substrate of postural instability.